Design and analysis of experiment - Dean,Angela; Daniel Voss (New Delhi: Springer, 2014)
The design and analysis of experiments is an essential part of investigation and discovery in science, of process and product improvement in manufacturing, and of comparison of competing protocols or treatments in the applied sciences. This book offers a step by step guide to the experimental planning process and the ensuing analysis of normally distributed data. Design and Analysis of Experiments emphasizes the practical considerations governing the design of an experiment based on the objectives of the study and a solid statistical foundation for the analysis.
Principles and techniqes -- Planning Experiments -- Designs with one source of variation -- Inferences for contrasts and treatment means -- Checking model assumptions -- Experiments with two crossed treatment factors -- Several crossed treatment factors -- Polynomial regression -- Analysis of covariance -- Complete block designs -- Incomplete block designs -- Designs with two blocking factors -- Confounded two-level factorial experiments -- Confounding in general factorial experiments -- Fractional factorial experiments -- Response surface methodology -- Random effects and variance components -- Nested model -- Split-plot designs
Includes bibliography and index
Keywords: Statistics; Design of Experiments